LIGHT RARE EARTH ELEMENT DEPLETED TO ENRICHED BASALTIC FLOWS FROM 2.8 TO 2.7 GA GREENSTONE BELTS OF THE UCHI SUBPROVINCE, ONTARIO, CANADA - Hollings P.; Kerrich R. (My University, 2006)
A compositionally diverse group of basaltic flows are present in the 2.7 Ga St. Joseph assemblage of the St. Joseph greenstone belt, Uchi Subprovince. A spectrum of light rare earth element (LREE) depleted to enriched patterns corresponds to low-, medium- and high-K series (LKS, MKS, HKS) basalts, shoshonites and leucitites of some modern arcs. More primitive, tholeiitic LKS and MKS basalts plot with counterparts from modern intraoceanic arcs, such as the South Sandwich Islands, and show no evidence of contamination by continental crust. Consequently they are interpreted to have erupted in an oceanic setting. There is an array from low Nb with high Zr/Nb (29) to high Nb but lower Zr/Nb (15) indicative of a mantle wedge similar to average mid ocean ridge basalts (MORB; average Zr/Nb = 32). These basalts also show positive to negative Nb, Hf and Zr anomalies. Negative anomalies are interpreted as the product of first stage melting, where LREE and MREE are added to the mantle wedge from dehydration of the slab, leaving a residue with high Nb/La, Hf/Nd and Zr/Nd. Second stage melts inherit the high HFSE/REE ratios. Within the Birch-Uchi greenstone belt, basalts of the ~2.8 Ga Woman assemblage includes both LKS and HKS. These are characterized by similar Nb-Zr/Nb and HFSE/REE systematics, signifying that these are general features of sub-arc mantle wedges that developed over 100 Ma in Uchi subprovince arcs. Enriched St. Joseph assemblage basaltic rocks cannot stem from sediment melting on the slab, as Th/Ce ratios are generally < 0.1. Neither can they derive from an ocean island basalt component because Nb anomalies do not correlate with La/Ybn. Rather, the trend from primitive LKS through MKS to HKS, leucitite and shoshonite is interpreted to reflect progressively lower degrees of partial melting at increasing depths and/or less depleted mantle wedge. © 2005 Elsevier B.V. All rights reserved.
Keywords: BASALTS; GEOCHEMISTRY; ISLAND ARCS; SHOSHONITES; SUPERIOR PROVINCE; UCHI SUBPROVINCE